Using Evaluation Models to Assess Behaviors’ Development in Moral Education - Mustakim, Siti Salina; Hao, Tham Jia; Minghat, Asnul Dahar; Zulkarnain, Izhan Iskandar (International Journal of Psychosocial Rehabilitation, 2020)
Moral Education is one of the value education programs in Malaysia, especially for non-Muslim students. The program aims to produce non-Muslim students who have moral values through the practice of moral values in daily life. This paper discussed the crucial development of moral education aspired by the seven key principles as a guideline in generating a comprehensive human intellectual, emotional, spiritual, and social well-being. Relevant theories, models, and approaches are discussed towards developing moral’s behavior in Moral Education.